Análisis de riesgos en operaciones de reparación de pcb’s en el laboratorío electrónico de la cnt - Cevallos Valdez, Angel (2010)
In the electronic factories, accessories and electrical tools of repair, mechanicals and chemicals substances, are used generally which they are generating environmental contamination that directly affects to the technician and its surroundings. In the majority of the repair shops in which it is fixed printed electronic board,s generally ambient are closed, small and in addition little ventilated, failing to fulfill therefore the specific norms for the good practice in a Laboratory of Electronics. The laboratory of the CNT not difference to the others as far as the tools and others, reason why has been created the necessity to generate a quantitative analysis of potential risk,s using the parameters of the pertinent norms as they are the OSHAS, Código Nacional de Trabajo, Normas de Obras Publicas y construcción, Normas de Higiene Laboral. This way, procedures are created for providing to the company a useful tool for the correct practice and security of the Technician as the one of their environment.